Estudo da função lisossomal em um modelo celular de Doença de Parkinson - Nascimento, Ana Carolina [UNIFESP] (2019)
Parkinson's disease (PD) is a neurodegenerative disease characterized by the progressive loss of dopaminergic neurons in the substantia nigra pars compacta. One of the histopathological hallmarks of Parkinson's disease is the accumulation of α-synuclein in the cytoplasm of neurons, with the presence of protein aggregates called Lewy Bodies. The α-synuclein has a role in synaptic transmission, however mutations in SNCA gene may lead to the expression of mutant types, such as A30P and A53T, which are related to autosomal dominant PD. Lysosomal dysfunctions have been described in PD and they are also related to the α-synuclein protein. The aim of this work was to study the morphological and functional alterations of lysosomes in a PD cell model, SH-SY5Y cells overexpressing the α-synuclein protein WT or its mutants forms, A30P and A53T. For this purpose, real time fluorescence microscopy, western blot, immunofluorescence and confocal microscopy techniques were performed. Our data showed that the cytosolic Ca2+ variation by endoplasmic reticulum (ER)-Ca2+ release agent of cells that overexpressed α-synuclein WT, A30P and A53T was lower than control cells, indicating a reduced capacity of ER Ca2+ buffering. However, there was an increase of the release of Ca2+ from lysosomes in the PD model, indicating an attempt to buffer the ion that presents altered homeostasis. In addition, cells that overexpressed the α-synucleins proteins had a reduction in lysosomal marker (LAMP1) and the data indicate an increase in lysosomal pH. Such changes were more pronounced in A53T cells. Regarding to morphology, WT cells presented larger lysosomes than control cells. Altogether, the results showed that the overexpression of protein α-synuclein WT or its mutants A30P and A53T promotes lysosomal dysfunctions and this can contribute to pathogenesis of PD.